Metafora pada Novel Mêndhung Kêsaput Angin Karya A.G Suharti: Kajian Semantik Kognitif - Mahanani, Endah Normawati; Setyanto, Suroto Rosyd (STKIP PGRI Ponorogo Press, 2024)
This research was conducted to described metaphors in the novel Mêndhung Kêsaput Angin by A.G. Suharti. Novel writing certainly uses archaic language which is synonymous with the use of metaphor. Researchers describe the use of metaphors in novels written in 1980. The method used is a qualitative descriptive research method. The data source is the novel Mêndhung Ksaput Angin by A.G. Suharti, while the data are phrases, clauses or sentences that contain metaphors. The theory used refers to Peter and Newmark's theory in Parera about imagery in metaphor, while Lakoff and Johnson are used as supporting theories. The results of this research are (1). there are 36 data or forms of metaphor in the metaphor analysis in the novel